Profile of Nursing research groups of the National Council for Scientific and Technological Development - Andréia Cristina Barbosa Costa; Erika de Cássia Lopes Chaves; Fábio de Souza Terra; Fábio de Souza Terra (Universidade Federal do Ceará, 2014)
Nursing has been developing in the research field, therefore, it is important to be inserted into a research group of the National Council for Scientific and Technological Development, a funding agency that supports studies and strengthens the knowledge. This is a descriptive, retrospective and cross-sectional study that aimed to investigate the profile of Nursing research groups registered in the National Council for Scientific and Technological Development. A survey of data from research groups in Nursing took place in the first half of 2012, finding 440 groups. The Southeast region was the one that presented more research groups registered (49.5%). The leaders of the groups had from one to ten productions with Impact Factor (49.1%). It is concluded that Nursing is expanding in the research field, and that many Brazilian regions need to be encouraged, as this is a form of developing the area.